ObjectiveTo establish a nomogram for predicting the risk of post-hepatectomy complications (PHC) in hepatic echinococcosis by analyzing the risk factors for PHC in two types of hepatic echinococcosis, and to investigate its value in clinical practice. MethodsA retrospective analysis was performed for the clinical data of 263 patients with two types of hepatic echinococcosis who underwent hepatectomy in Qinghai University Affiliated Hospital from January 2015 to August 2020, and among these patients, 93 were enrolled as PHC group and 170 were enrolled as control group. The Mann-Whitney U test was used for comparison of non-normally distributed continuous data between two groups, and the independent samples t-test was used for comparison of normally distributed continuous data between two groups; the chi-square test and the Fisher’s exact test were used for comparison of categorical data between two groups. Univariate and multivariate logistic regression analyses were used to screen out independent risk factors for PHC, and a nomogram risk prediction model was established based on the weight of each independent risk factor. The Bootstrap resampling method was used for internal verification of the model; the receiver operating characteristic (ROC) curve was plotted to evaluate the discriminatory ability of the model; calibration curve and the Hosmer-Lemeshow test were used to evaluate the consistency of the model; decision curve analysis (DCA) was performed to verify the clinical effectiveness of the model. ResultsAlbumin-bilirubin (ALBI) score (odds ratio ［OR］=3.694, 95% confidence interval ［CI］: 1.860-7336, P＜0.05), time of operation (OR=2.848, 95%CI: 1.384-5.859, P＜0.05), intraoperative blood loss (OR=4.832, 95%CI: 2.384-9.793, P＜0.05), and hydatid diameter (OR=3.073, 95%CI: 1.528-6.177, P＜0.05) were independent risk factors for PHC in two types of hepatic echinococcosis. A nomogram risk prediction model was established based on the weight of the above four independent risk factors, and the model had an area under the ROC curve of 0.877 (95%CI: 0.831-0.923). The model had a consistency index of 0.871 after internal verification using the Bootstrap resampling method, suggesting that the model had good discriminatory ability. The fitting of the observed value and the actual value of the calibration curve and the Hosmer-Lemeshow test (P=0.905) showed that the predicted value of the nomogram risk prediction model had good consistency with the actual observed value. When the threshold probability was 35.6%, DCA showed a net clinical benefit of 22%, and the model had good clinical applicability within the threshold probability ranging from 8% to 89%. ConclusionALBI score, time of operation, intraoperative blood loss, and hydatid diameter are independent risk factors for PHC in patients with two types of hepatic echinococcosis, and the nomogram risk prediction model established based on these factors has good accuracy, consistency, and clinical practicability. - LI Hongye (Editorial Department of Journal of Clinical Hepatology, 2021)
ObjectiveTo investigate the endoscopic ultrasound (EUS) features of distal biliary stricture (DBS), and to provide a clinical basis for the evaluation of DBS by EUS. MethodsRelated clinical data were collected from 175 patients with DBS who underwent EUS examination in The First Affiliated Hospital of Anhui Medical University from April 2016 to March 2020 to analyze their clinical manifestation, laboratory examination results, imaging findings, and EUS findings, and the patients were followed up to summarize the EUS features of DBS. The chi-square test was used for comparison of categorical data between groups, and the t-test was used for comparison of continuous data between groups. ResultsAmong the 175 patients with DBS, 85(48.57%) had benign DBS and 90(51.43%) had malignant DBS. Compared with the patients with benign DBS, the patients with malignant DBS had a significantly longer length of stricture on EUS (14.1±3.0 mm vs 7.9±3.0 mm, t=13.358, P＜0.001) and significantly higher incidence rates of the characteristic changes on EUS such as hypoechoic space-occupying lesions in lumen (57.8% vs 34.1%, χ2=9.843, P=0.002), peripheral lymph node enlargement (26.7% vs 12.9%, χ2=5.147, P=0.023), and pancreatic duct dilatation (51.1% vs 28.2%, χ2=9.532, P=0.002). EUS combined with magnetic resonance cholangiopancreatography had a sensitivity of 70.6% in the diagnosis of benign DBS and a sensitivity of 922% in the diagnosis of malignant DBS. ConclusionThe characteristic EUS features of DBS, such as long length of stricture, hypoechoic lesion, peripheral lymph node enlargement, and pancreatic duct dilatation, may help with the differential diagnosis of DBS in clinical practice.